Financial Reporting Design at UD. Madu Segoro Based on Microsoft Excel Application - Abdillah, M.Rickwan; Probowulan, Diyah; Halim, Moh (West Science Accounting and Finance, 2024)
Draft financial reporting at UD Madu Segoro by carrying out Microsoft Excel-based financial records in accordance with Financial Accounting Standards of Micro, Small and Medium Enterprises/SAK-EMKM. The implementation of Microsoft Excel-based financial recording aims to improve the capabilities of SME, especially UD. Madu Segoro in improving the ability to make recording financial reports easier, Avoid damaged and lost files. The method used in implementing financial recording at UD. Madu Segoro/SME is carried out in four stages, namely: identifying the research question, Interview the information to answer the question, analyzing in-terpreting the information,and sharing the results with the business owner.